1995
DOI: 10.1093/oxfordjournals.humrep.a136070
|View full text |Cite
|
Sign up to set email alerts
|

Ethics and society: Review of the organized support network for infertility patients in licensed units in the UK

Abstract: In acknowledging that 'counselling is generally recognized as beneficial', the Human Fertilization and Embryology Authority (HFEA) Code of Practice requires that all infertility units provide counselling facilities to be available for patients. In this study, we intended to evaluate the support and counselling services made available by the licensed units in the UK. A questionnaire consisting of 30 questions was designed and sent to every licensed treatment unit in the UK. The data were coded on a nominal scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…These results are consistent with past research from the U.K. (7,17). Also, as seen in past research, distressed patients were more likely than nondistressed patients to receive MHS (30).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with past research from the U.K. (7,17). Also, as seen in past research, distressed patients were more likely than nondistressed patients to receive MHS (30).…”
Section: Discussionsupporting
confidence: 91%
“…Since then, many additional studies have revealed high rates of psychologic distress in fertility treatment patients (3)(4)(5)(6). The need for help with the emotional aspects of infertility has been endorsed by professional groups, government authorities, and patients themselves (7)(8)(9)(10). Benefits of MHS for fertility treatment patients have been demonstrated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Counselling has received recognition for its role in the assisted conception technique process [4,10–13] and those using the techniques are thought to be in favour of counselling [5,14,15]. Yet, during recent Parliamentary discussions, it was suggested that the utilization of counselling can vary between 2% and 40% [16], which concurs with studies conducted in clinics in the UK [17]. A number of factors are thought to influence whether people access counselling or not, such as the timing of it [3,14,18,19]; the perception of the techniques [20,21]; and the relationship between clinicians and counsellors within clinics [16,22,23].…”
Section: Introductionmentioning
confidence: 87%
“…Human Fertilization and Embriology Authority (HFEA) recommend sociopsychological consultation for patients undergoing IVF. However, the system of psychological help to females involved in IVF is still underdeveloped [9,13].…”
Section: Introductionmentioning
confidence: 99%